A review of the international FLOSS (Free/Libre Open Source Software) innovation surveys - Morero, Hernan (2018)
Given the substantial growth that software and IT sector has had in the last decade, it becomes relevant to measure the impact that this expansion has had on the development of emerging economies. Specifically, the study of the FLOSS production activity is relevant given its contribution to the Knowledge Intensive Services Sector. The aim of this study is to design an innovation survey for the software sector that considers the FLOSS activity separately. Moreover, the paper describes an extensive systematization, evaluation and analysis of diverse technological surveys carried out on the software activity and the FLOSS surveys available specified at a firm level, as a way to collect all the possible background which allows proposing a questionnaire that measures the particularities of FLOSS.